2019
DOI: 10.1007/s00268-019-04940-0
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Propensity‐Score Matched Study of Mesh Versus Suture Repair of Primary Ventral Hernias in Women with a Subsequent Pregnancy

Abstract: Background Mesh reinforcement is recommended for repair of primary ventral hernias; however, this recommendation does not consider a potential subsequent pregnancy. The aim of this prospective cohort study was to compare mesh and suture repair of a primary ventral hernia in women with a subsequent pregnancy. Methods All women of childbearing age who underwent repair of a primary ventral hernia between 2007 and 2014 were identified in the Danish Ventral Hernia Database. Data were merged with the Danish Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…The cumulative reoperation rate for recurrence was 16 per cent after mesh repair and 11 per cent after suture repair (adjusted for BMI and hernia defect size). In contrast, in a recent questionnaire study, 195 women of childbearing age with a history of umbilical or epigastric hernia repair who subsequently became pregnant were compared with a propensity‐matched controlled group of 246 women; the use of mesh was found to be independently associated with reduced recurrence rates. However, the use of mesh was associated with an increased risk of chronic pain (17·5 per cent) compared to that for suture repair (9·5 per cent) when having a subsequent pregnancy.…”
Section: Resultsmentioning
confidence: 93%
“…The cumulative reoperation rate for recurrence was 16 per cent after mesh repair and 11 per cent after suture repair (adjusted for BMI and hernia defect size). In contrast, in a recent questionnaire study, 195 women of childbearing age with a history of umbilical or epigastric hernia repair who subsequently became pregnant were compared with a propensity‐matched controlled group of 246 women; the use of mesh was found to be independently associated with reduced recurrence rates. However, the use of mesh was associated with an increased risk of chronic pain (17·5 per cent) compared to that for suture repair (9·5 per cent) when having a subsequent pregnancy.…”
Section: Resultsmentioning
confidence: 93%
“…Controversies have been raised regarding the benefit of routine mesh placement in both large and small umbilical hernia repair. Mesh placement has been shown, even in small ventral hernias with fascial defect <2 cm, to reduce likelihood of recurrence especially during subsequent pregnancy but is associated with higher chance of chronic post‐operative pain 13 and post‐operative wound infection. Others suggest that mesh placement is not associated with significant impact on subsequent pregnancies and labour course itself 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…This risk of recurrence may be increased in the presence of diastasis recti; hence, mesh repair is recommended in this situation [9]. Mesh repair might reduce the recurrence risk but can cause chronic pain [25]. However, another study revealed that mesh repair was not associated with a reduction in the recurrence risk [26].…”
Section: Suture Versus Mesh Repairmentioning
confidence: 99%